In-vitro Antimicrobial Activity of Novel Quinazoline Derivatives: One-Pot Synthesis and Characterization (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Designing an efficient class of novel antimicrobial agents becomes an enormous task in pharmaceuticals research and development. Current research work comprised of finding a novel series of various substituted quinazoline derivatives. The synthetic scheme involves single-step, one-pot synthesis involving the condensation of highly activated aromatic amide starting materials with weakly nucleophilic alkyl nitriles to directly provide the corresponding quinazoline derivatives employing trifluoromethanesulfonic anhydride catalyst. All the synthesized compounds were characterized by IR, proton nuclear magnetic resonance (1HNMR) and message, audience, situation, significance (MASS) spectral methods and screened for antimicrobial activity against four bacterial strains Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and two fungal strains Aspergillus niger and Candida albicans. All the compounds displayed decent antimicrobial profile when compared with the standard drugs neomycin and nystatin. Among the synthesized compounds (3a1-3a5&3b1-3b5) evaluated, compounds 3a1, 3a2, 3a3, 3b1and 3b2 have demonstrated decent antimicrobial activity against selected strains of bacteria and fungi.